1997
DOI: 10.4141/s97-002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and spatial variations in soil nitrogen and phosphorus supply rates in a boreal aspen forest

Abstract: spatial variations in soil nitrogen and phosphorus supply rates in a boreal aspen forest. Can. J. Soil Sci. 77: 597-612. Soil nitrogen (N) and phosphorus (P) supply is one of the growth limiting factors in many forest ecosystems. Seasonal patterns in soil N and P supply rate were examined during a 2-yr period (1994)(1995) for forest floor (L, F and H) and upper mineral (Ae) horizons in an 80-yr-old aspen forest in Saskatchewan, Canada. Accumulation of plant nutrient ions on ion exchange resins incubated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 50 publications
0
18
1
Order By: Relevance
“…Nutrient uptake by the membranes will depend on ion diffusion in the soil, which may be diminished in dry conditions (Subler et al, 1995). Low diffusion of ions in dry soils also affects root uptake, which makes resin membranes a good index of flow capacity and ion availability for plants in soils (Huang and Schoenau, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient uptake by the membranes will depend on ion diffusion in the soil, which may be diminished in dry conditions (Subler et al, 1995). Low diffusion of ions in dry soils also affects root uptake, which makes resin membranes a good index of flow capacity and ion availability for plants in soils (Huang and Schoenau, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The use of these ionic exchange membranes (IEMs) provides one of the most reliable indices of plant nutrient availability (Ziadi et al, 1999(Ziadi et al, , 2000Qian and Schoenau, 2002). IEMs simulate the flux of nutrients into roots (Huang and Schoenau, 1997). Compared with soil resource sampling methods commonly used (e.g., soil cores or buried resin-filled bags), the advantages of IEM spikes include inflicting minimal damage on the soil, being simple to use, and allowing intensive sampling over multiple time periods at the same spatial locations (Cain et al, 1999).…”
Section: Field Sampling and Lab Analysismentioning
confidence: 99%
“…This observation agrees with the findings of Mitchell et al [21] who observed high NO 3 − concentration and flux in spring and low NO 3 − flux in summer and autumn. On the contrary, Huang and Schoenau [24] reported minimal soil NO 3 − supply in May and maximum supply later in the growing season in an aspen forest in Saskatchewan, Canada. Unlike the findings of Mitchell et al [21], the decline in NO 3 − supply rate in August in this study cannot be attributed to vegetation uptake alone because the index of NO 3 − uptake was also higher in May than in August and October.…”
Section: Seasonal Dynamics In Soil Supply and Bioavailability Of N Pmentioning
confidence: 92%
“…On the contrary, Zhao et al [25] found greater mineral P in the summer and attributed it to the combined effect of the high temperature and moisture which promote the biological transformations of soil P and lead to increased availability of inorganic P in the soil. However, other researchers have observed greater P accumulation during autumn than in spring and summer [24,26] and ascribed it to the greater plant uptake and increased biological activity in the soil.…”
Section: Seasonal Dynamics In Soil Supply and Bioavailability Of N Pmentioning
confidence: 93%
“…In many instances, some nutrients can be made available to plants through disturbance, although nitrogen requires atmospheric or biotic input (Ballard 1980). Litterfall is a significant step in nutrient cycling; nutrients return to the forest floor in organic form, where mineralization makes them available to plants (Huang and Schoenau 1997). A meta-analysis of the removal of harvest residues found a sl ight decrease in nitrogen, whereas leaving residue showed an increase in total nitrogen in forest soils.…”
Section: Soil P Rop Ertiesmentioning
confidence: 99%